2019
DOI: 10.3390/ijerph16071142
|View full text |Cite
|
Sign up to set email alerts
|

A Survey on Satisfaction of Type 2 Diabetes Patients with Different Demographic Variables to Medical Services

Abstract: Taking Type 2 diabetes as the research object, and through questionnaire interviews, this study sought to determine the degree of satisfaction of patients with different attributes with medical services according to the distribution of demographic variables. Finally, the statistical results were taken as the reference basis for medical personnel to provide care to patients. Regarding the questionnaire survey, the questionnaire items were designed through face-to-face interviews aiming at their medical treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…[ 16 ] Satisfaction of patients was evaluated using 5-point system medical treatment process (very satisfied: 5 points; satisfied: 4 points; no comment: 3 points; dissatisfied: 2 points; very dissatisfied: 1 point). [ 17 ] Quality of life was accessed using 5 domains included energy, memory, diet, sex, and finance as described previously. [ 18 ] Systolic blood pressure (SBP) and diastolic blood pressure (DSP) were measured using the Spacelabs ambulatory BP monitor 90207 (Redmond, Wash).…”
Section: Methodsmentioning
confidence: 99%
“…[ 16 ] Satisfaction of patients was evaluated using 5-point system medical treatment process (very satisfied: 5 points; satisfied: 4 points; no comment: 3 points; dissatisfied: 2 points; very dissatisfied: 1 point). [ 17 ] Quality of life was accessed using 5 domains included energy, memory, diet, sex, and finance as described previously. [ 18 ] Systolic blood pressure (SBP) and diastolic blood pressure (DSP) were measured using the Spacelabs ambulatory BP monitor 90207 (Redmond, Wash).…”
Section: Methodsmentioning
confidence: 99%
“…Drug safety concerns should be closely monitored in elderly patients with the abovementioned conditions. Tu et al reported "A Survey on Satisfaction of Type 2 Diabetes Patients with Different Demographic Variables to Medical Services" [9]. This study used the SPSS statistical software (IBM, Armonk, New York, NY, USA) for analysis, and the results show that: (1) Patients of different genders had different degrees of satisfaction with medical services.…”
Section: The Topics Of Environmental Health Sciences and Public Healthmentioning
confidence: 92%
“…The survey was planned using face to face interviews. The questions were about different attributes of the hospital services to check whether a patient is happy with the hospital or not [23].…”
Section: Related Workmentioning
confidence: 99%